Teen Titans : Starfire - Book 5 - Garcia, Kami; Picolo, Gabriel; Haynes, Rob; Calderon, David; Abbott, Wes (Burbank, CA : DC Comics, 2024)
When Kori Anderson, who has a connective tissue disorder, and her popular older sister, Kira, participate in a pharmaceutical companys clinical trial, she begins to discover strange powers and hopes to discover the truth about these abilities--and her sisters boyfriend.
"Starfire created by Marv Wolfman and George Přez."
Ages 13-17
Grades 10-12
Keywords: Ability -- Comic books, strips, etc; Self-realization -- Comic books, strips, etc; Ehlers-Danlos syndrome -- Comic books, strips, etc; Graphic novels